DIFFICULTY IN DIAGNOSTICS TO VERIFY CROHN’S DISEASE IN CHILDREN. CLINICAL CASE STUDY - E.N. Fedulova; P.P. Potekhin; G.M. Lukoyanova; E.A. Rozhdenkin; O.A. Tutina; O.V. Fedorova; A.R. Bogomolov; S.A. Abramov; E.V. Lobanova; O.V. Shumilova (Педиатрическая фармакология)
Diagnostics of Crohn’s disease, especially in children, presents a big challenge, given the low prevalence rate of this disease, polymorphism of the clinical manifestation and insufficient alertness of primary pediatricians relative to this pathology. As a result, untimely diagnostics, and, therefore, inadequate treatment, the disease takes an unfavourable turn, complications develop resulting in disabilities of little patients. The provided material and described clinical case study help physicians to identify Crohn’s disease in due time and refer the patient to a specialised medical establishment for additional examination and determining treatment tactics.Key words: inflammatory bowel disease, Crohn’s disease, diagnostics, children. (Pediatric Pharmacology. – 2010; 7(2):115-122)